Occupational Health and Safety Practices in Architectural Restoration and Conservation Projects - Uzun, Mert; Ozturk, Deniz; Gurcanli, Gurkan Emre (TURKISH CHAMBER CIVIL ENGINEERS, 2020)
Preservation of historic buildings with their original state and conveyance that heritage to the next generations is the ultimate aim of the restoration projects. Restoration works requires special professional skills and the particular risks of these projects oblige peculiar occupational health and safety measures. Although, in Turkey, the architectural restoration works are regarded as a part of construction industry according to the legislation, research upon peculiar occupational health and safety measures are not sufficient. In this study, possible risks during architectural restoration projects were examined and those risks were classified as physical, chemical, biological and ergonomical risks according to legislative obligations as well as the data obtained from site observations. After the discussions upon these risks, a risk assessment guide and flowchart were established for healthy and safe restoration work.
Keywords: Construction industry; architectural restoration; occupational health and safety; risk analysis; Engineering